Ekāmra candrikā : Ekāmrakṣetraṣya tathā śrīliṅgarājadevasya vivaraṇasamvalitapaurāṇikaḥ granthaḥ - Ekāmracandrikā (Ratnākara Gargavaṭu; Prāptisthānaṃ Śrī Rādhāramaṇa-Pustakāḷaya, 1931)
On the significance of Bhubaneswar, Orissa, as the seat of Lingaraja, form of Siva, Hindu deity.